Informasi Obat pada Pasien Diabetes Mellitus Rawat Jalan di RSUD X Surabaya: Apa yang diberikan dan apa yang diketahui? - Shieny Agustin Santoso; Adji Prayitno Setiadi; Karina Kumaladewi Widjaja; Yosi Irawati Wibowo (Fakultas Farmasi Universitas Pancasila, 2023)
The prevalence of Diabetes Mellitus (DM) in Indonesia has increased 0.5% in the last five years. This study aimed to evaluate information provided and level of knowledge among DM patients on their treatment at the outpatient clinic at the X Public Hospital (Rumah Sakit Umum Daerah, RSUD), Surabaya, Indonesia. This was a cross-sectional study using a checklist developed by The Food And Drug Supervisory Agency which consists of 11 types of information. The data were analysed descriptively; to test the relationship between the amount of information provided and the patient's level of knowledge, Spearman correlation analysis was used. A total of 110 patients were included in this study (response rate 90.91%). The mean of information provided and understood by patients was 6.48/11±0.73 and 7.48/11±0.90, respectively. There was a significant relationship between information provided to and known by patients (p=0.001). Characteristic factors such as age (p=0.001), education level (p=0.001), and sources of information related to DM (p=0.014) were shown to influence DM patients' knowledge of their treatment. This study indicated the importance of providing clear and complete drug information, especially for patients on long-term therapy, to improve their knowledge, thus potentially increasing adherence and optimizing therapy outcomes.